ANALISIS HUKUM PIDANA TERHADAP PENCURIAN ARUS LISTRIK DI KOTA TERNATE - Muhammad Hi Jalal; Tri Syafari; Nam Rumkel (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Interpreting law enforcement as a process carried out in an effort to uphold or function real legal norms, which can serve as a guide in conducting relationships in the life of society and the state in various aspects. In Ternate City, current theft often occurs both on a large and small scale, it can be seen that since 2019, there have been two quite large cases of theft at PT Aneka Tambang and Bank Teras BRI Gamalama Terna, both cases can be categorized as acts theft is based on Law Number 30 of 2009 concerning Electricity, but there is no prosecution by PT Perusahan Listrik Negara or the legal investigation process carried out by the authorized party.